A review on women leaderships in patriarchal society: challenges and opportunities - Adzahar, Khairul Azfar; Jamaludin, Mohd Fazil; Saharan, Mohd Shafiz (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2024)
This article investigates the contradictory realities of female leadership in patriarchal cultures, delving into both the significant challenges and opportunities. Despite progress toward gender equality, women leaders confront persistent challenges, such as gender stereotypes, underrepresentation, work-life balance concerns, and systemic discrimination (Galsanjigmed & Sekiguchi, 2023). These difficulties are worsened by the widespread biases that impede their professional growth. The article highlights the impact of female leaders on society despite the fact that women only hold 28.2% of managerial jobs globally (UN Women, 2023). With their unique perspectives and inclusive approach to leadership, they may promote gender equality, advance society, and inspire future generations. Through a balanced review of the opportunities and challenges, the article aims to present a nuanced representation of the environment for women leaders in a patriarchal society, highlighting the need for systemic change to truly achieve gender parity.